Cutting-down the energy consumption of electrohydrodynamic drying by optimizing mesh collector electrode. (1st October 2020) - Iranshahi, Kamran; Martynenko, Alex; Defraeye, Thijs
Abstract: Drying is one of the most energy-intensive processes in the multiple industries, due to the high latent heat required to evaporate the water, which is often done by employing hot-air drying. Electrohydrodynamic (EHD) drying is an alternative, innovative drying technology with large potential for industrial application and lower energy consumption. EHD drying is non-thermal, which makes this technology particularly suitable for drying of heat-sensitive biomaterials. A key bottleneck for EHD drying is the process scalability in order to uniformly dry large amounts of product, which is limited by the geometrical design of the collector electrode. To overcome this challenge, a recently introduced electrode configuration – a mesh collector – is further optimized in order to significantly reduce the energy consumption of the process. Exergy analysis was used to identify the energy conversion losses in ion production, ionic flow generation, and convective dehydration stages of fruit. As a result, a much more energy-efficient mesh configuration was designed. This improved design resulted in a similar drying rate as a normal mesh collector but showed a seven times smaller energy consumption. This upscalable, cleaner, and also much more energy-efficient EHD dryer design paves the way for industrial prototypes and pilot plants. Highlights: An up-scalable configuration for Electrohydrodynamic drying is proposed. Comprehensive electrostatics, aerodynamics, and exergy analyses are performed. The geometrical parameters of the mesh do not affect the dehydration kinetics. The proposed configuration shows a significant improvement in energy consumption.